2019
DOI: 10.1002/ange.201902324
|View full text |Cite
|
Sign up to set email alerts
|

Solar‐Driven Water–Gas Shift Reaction over CuOx/Al2O3 with 1.1 % of Light‐to‐Energy Storage

Abstract: Hydrogen production from coal gasification provides a cleaning approach to convert coal resource into chemical energy, but the key procedures of coal gasification and thermal catalytic water–gas shift (WGS) reaction in this energy technology still suffer from high energy cost. We herein propose adopting a solar–driven WGS process instead of traditional thermal catalysis, with the aim of greatly decreasing the energy consumption. Under light irradiation, the CuOx/Al2O3 delivers excellent catalytic activity (122… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Therefore, the maximum intensity of the electric field over LD‐Cu in Figure 3c and 3d was much higher (≈62) than that around a single supported Cu nanoparticle. The results suggest that the visible‐light absorbing Cu nanoparticles in LD‐Cu acted as the hot electron source and active sites in the WGSR, unlike Ouyang et al.‘s work where UV absorption by CuO x semiconductors created conduction band electrons which then participated in the WGSR [5e] …”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, the maximum intensity of the electric field over LD‐Cu in Figure 3c and 3d was much higher (≈62) than that around a single supported Cu nanoparticle. The results suggest that the visible‐light absorbing Cu nanoparticles in LD‐Cu acted as the hot electron source and active sites in the WGSR, unlike Ouyang et al.‘s work where UV absorption by CuO x semiconductors created conduction band electrons which then participated in the WGSR [5e] …”
Section: Resultsmentioning
confidence: 67%
“…However, whilst of fundamental interest, the rates of hydrogen production in the photocatalytic WGSR studies are far below industry levels [5a–d] . In contrast, Cu‐based photothermal WGSR catalysts (CuO x semiconductors) operating at 250–350 °C under light irradiation yielded H 2 production rates close to traditional high‐temperature thermal catalysts [5e–g, 6] . However, the performance of these photothermal WGSR catalysts at lower temperatures (<250 °C) was inferior to thermal nobel metal‐based catalysts [2, 7] .…”
Section: Introductionmentioning
confidence: 99%
“…The lattice fringe of ∼0.208 nm could be clearly observed from the TEM image of the reduced catalyst (Figure 2A), which was assigned to the (111) plane of the cubic Cu. 40 As shown in Figure 2B−E, the Cu 0 nanoparticles were evenly dispersed on the surface of the CuAl and CuZnAl-x samples. Generally, the role of Zn species is to inhibit the aggregation of Cu 0 nanoparticles during the reduction, to form small Cu 0 nanoparticles.…”
Section: Structural Characterization Of the Catalystsmentioning
confidence: 86%
“…Nevertheless, the hydrogen production rates achieved through photocatalysis fall significantly below industry standards. [84][85][86][87][88] In contrast, Cu-based photothermal catalysts for WGS have shown the ability to produce hydrogen at rates comparable to those of traditional high-temperature thermal catalysts when operated under light irradiation at 250-350 1C. 85,86,89,90 The group led by Ye reported that CuO x /Al 2 O 3 exhibits excellent catalytic activity (122 mmol g cat À1 s À1 H 2 evolution and 495%…”
Section: Co Conversionmentioning
confidence: 99%